Outreach and performance analysis of microfinance institutions in Cameroon - Shu, Cletus Ambe (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: Since people with low incomes do not have access to financial institutions and in most developing countries, only public workers benefit from the services of public banks, the poor and private workers with low incomes cannot borrow from these public banks. Hence, micro financial institutions have become the answer to those who cannot benefit from the financial services of the public banks. This study tries to compare the performance and outreach aspect of the micro financial institutions in Cameroon against the African benchmark. Furthermore, it investigates if there is a tradeoff between performance and outreach. A total of 6 selected micro financial institutions with branches all over Cameroon were chosen for this study. Using the difference of mean test, the findings of the study revealed that generally, the micro financial institutions in Cameroon implemented a low cost strategy and are heavily exposed to default risk. We also concluded a tradeoff between the performance and outreach factors. Micro financial institutions in Cameroon are more focus at making profits rather than reaching out to the poorest of the poor in the communities. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Gelişmekte olan birçok ülkede düşük gelirli insanların finansal kurumlara erişimi mümkün değildir ve sadece kamu çalışanları, kamu bankalarından yararlanabilmektedir. Düşük gelirli insanlar ve özel sektör çalışanları kamu bankalarından yararlanamamaktadır. Bundan dolayı, kamu bankalarından yararlanamayanlara mikrofinansal kurumlar çare olmuştur. Bu çalışma, Kamerun‘daki mikrofinansal kurumların performansını ve erişim yönünü Afrika kriterleri göz önünde bulundurularak karşılaştırılmaktadır. Bunun yanında, performans ve erişim arasında etkileşim olup olmadığını incelemektedir. Bu çalışma için Kamerun‘daki şubeleriyle birlikte 6 mikro finans kurumu seçilmiştir. Ortalama test farkı kullanılarak elde edilen sonuçlara göre, Kamerun‘daki mikro finansal kurumlar düşük maliyet stratejisi uygulamakta ve temerrüt riskine maruz kalmaktadır. Ayrıca performans ve erişim faktörleri arasında bir etkileşim görülmektedir. Kamerun‘daki mikro finansal kurumlar en yoksul kişiye kadar ulaşma yerine kar elde etmeye odaklanmıştır.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2012. Supervisor: Assist. Prof. Dr. Bilge Oney.
Keywords: Micro Finance Institutions - Cameroon; Banks and Banking - Cameroon; Microfinance - Outreach - Performance - Banks - Cameroon